New records for gray mouse opossum (Tlacuatzin canescens) in Sonora, México - Gutiérrez-González, Carmina E.; Kelley, Elise; Gómez-Ramírez, Miguel Á.; Mora-Carrillo, Federico (Therya Notes, 2022)
The gray mouse opossum (Tlacuatzin canescens) is one of the smallest marsupials in México. It is found primarily along the Pacific littoral zone and the neighboring coastal mountain range, from Alamos, Sonora southward to Oaxaca and Chiapas, as well as in isolated populations on the Tres Marias Islands and in the northern part of the Yucatán Peninsula. The new records of T. canescens were mainly acquired from long-term motion-triggered camera monitoring on the Northern Jaguar Reserve and ranches participating in the Viviendo con Felinos® program, which monetarily compensates ranchers for supporting the protection of wildlife, especially felines on their property. We documented 7 new records of T. canescens in Sahuaripa, Sonora. Three motion-triggered camera records, 3 dead encounters, and 1 live encounter in the Northern Jaguar Reserve obtained between 2015 and 2020. The new T. canescens records correspond to a northward range expansion for the species of at least 240 km beyond the previously known species’ range. The Northern Jaguar Reserve, whose mission is to protect part of the northern jaguar (Panthera onca) population, also represents a refuge for smaller species such as the gray mouse opossum, which is a Mexican endemic marsupial.